Observations of Magnetic Flux Ropes Opened or Disconnected From the Sun by Magnetic Reconnection in Interplanetary Space - Feng, Hengqiang; Zhao, Yan; Wang, Jiemin; Liu, Qiang; Zhao, Guoqing (Frontiers in Physics, 2021)
During solar eruptions, many closed magnetic flux ropes are ejected into interplanetary space, which contribute to the heliospheric magnetic field and have important space weather effect because of their coherent magnetic field. Therefore, understanding the evolution of these closed flux ropes in the interplanetary space is important. In this paper, we examined all the magnetic and plasma data measured in 1997 by the Wind spacecraft and identified 621 reconnection exhausts. Of the 621 reconnection events, 31 were observed at the boundaries of magnetic flux ropes and were thought to cause the opening or disconnection magnetic field lines of the adjacent ropes. Of the 31 magnetic reconnection events, 29 were interchange reconnections and the closed field lines of these related flux ropes were opened by them. Only 2 of the 31 magnetic reconnection events disconnected the opened field lines of the original flux ropes. These observations indicate that interchange reconnection and disconnection may be two important mechanisms changing the magnetic topology of the magnetic flux ropes during their propagation during the interplanetary space.